MANAJEMEN PENINGKATAN MUTU MADRASAH TSANAWIYAH DI KABUPATEN MESUJI: Indonesia - Latiful Wahid (STIT PRINGSEWU, 2023)
ABSTRACK The purpose of this study was to determine the planning, organizing, implementing, monitoring and evaluating quality improvement at Madrasah Tsanawiyah in Mesuji District. The method used in this study is a qualitative research method used to describe, describe, explore and describe the implementation of quality improvement management at Madrasah Tsanawiyah in Mesuji District. The conclusions in this study are 1). Planning to improve the quality of Madrasah Tsanawiyah education in Mesuji Regency is carried out with various considerations. 2). Organizing is carried out by detailing all the work that must be carried out by each individual in achieving the goals of the Madrasah. 3). The implementation of improving the quality of education at Madrasah Tsanawiyah in Mesuji Regency is a process of controlling educational institutions that run according to predetermined paths and reach their goals effectively and efficiently. 4). supervision of improving the quality of education at Madrasah Tsanawiyah in Mesuji Regency is carried out by taking into account the supporting and inhibiting factors of the management implementation process. 5). Evaluation is reviewing the policy of the Madrasah head in carrying out the mandate, determining the Madrasah program. Keywords: education quality improvement management ABSTRAK Penelitian ini bertujuan untuk menyelidiki perencanaan, pengorganisasian, pelaksanaan, pengawasan, dan evaluasi peningkatan mutu di Madrasah Tsanawiyah di Kabupaten Mesuji. Metode yang digunakan dalam penelitian ini adalah penelitian kualitatif yang berfungsi untuk menggambarkan dan menjelaskan implementasi manajemen peningkatan mutu di Madrasah Tsanawiyah di Kabupaten Mesuji. Hasil dari penelitian ini menunjukkan beberapa kesimpulan: 1) Perencanaan peningkatan mutu pendidikan di Madrasah Tsanawiyah di Kabupaten Mesuji dilakukan dengan mempertimbangkan berbagai aspek. 2) Pengorganisasian dilakukan dengan mendetailkan tugas dan tanggung jawab setiap individu dalam mencapai tujuan Madrasah. 3) Pelaksanaan peningkatan mutu pendidikan di Madrasah Tsanawiyah di Kabupaten Mesuji adalah proses mengendalikan institusi pendidikan agar berjalan sesuai dengan jalur yang telah ditetapkan dengan efektif dan efisien. 4) Pengawasan peningkatan mutu pendidikan di Madrasah Tsanawiyah di Kabupaten Mesuji dilakukan dengan memperhatikan faktor-faktor yang mendukung dan menghambat implementasi manajemen. 5) Evaluasi melibatkan peninjauan ulang kebijakan kepala Madrasah dalam menjalankan amanah dan menentukan program Madrasah.. Kata Kunci : manajemen peningkatan mutu pendidikan